Contributions from continuing training to pedagogical practice of teachers in a Santa Maria school (Research, Society and Development, 2020)
This article is part of a research paper from the Master of Humanities and Languages course of Franciscan University. The study made it possible to discuss the theme of the Reggio Emilia Workshops in continuing education meetings with teachers and managers of a preschool. The research is a qualitative approach, like a case study conducted in a preschool in Santa-Maria / RS where five teachers and one manager were interviewed. To interpret the results, Bardin (2010) content analysis was used. Such research highlights the importance of the exchange of experiences between teachers as the north for the continuing formation of teachers. It also highlights the relevance of the connection and sharing of knowledge between school management and other teachers beyond the protagonism of these professionals. It is concluded that the continuing training with the theme of the Workshops came to assist in the practice of the teaching staff of the institution and bring new ways of acting and mediate the work in the classroom awakening new learning possibilities with the children.